2015
DOI: 10.1007/s40265-015-0474-y
|View full text |Cite
|
Sign up to set email alerts
|

Flibanserin: First Global Approval

Abstract: Flibanserin (Addyi™) is chemically described as a benzimidazole and is being developed by Sprout Pharmaceuticals for the treatment of hypoactive sexual desire disorder (HSDD). The drug has a high affinity for serotonin 5-HT1A and 5-HT2A receptors (5-HT1A agonist/5-HT2A antagonist) and is believed to treat HSDD by increasing levels of dopamine and noradrenaline and lowering levels of serotonin in the brain. Flibanserin has been approved in the USA for the treatment of premenopausal women with acquired, generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
0
27
0
1
Order By: Relevance
“…For two reasons, subsequent studies evaluated effects of repeated flibanserin doses. First, flibanserin dosing guidelines in humans call for repeated dosing, and full effects of flibanserin on sexual behavior in preclinical studies are also seen primarily following repeated dosing [23]. Second, we have shown previously that repeated drug treatment can unmask expression of abuse-related ICSS rate-increasing effects of some other drugs such as mu opioid receptor agonists [2427].…”
Section: Introductionmentioning
confidence: 99%
“…For two reasons, subsequent studies evaluated effects of repeated flibanserin doses. First, flibanserin dosing guidelines in humans call for repeated dosing, and full effects of flibanserin on sexual behavior in preclinical studies are also seen primarily following repeated dosing [23]. Second, we have shown previously that repeated drug treatment can unmask expression of abuse-related ICSS rate-increasing effects of some other drugs such as mu opioid receptor agonists [2427].…”
Section: Introductionmentioning
confidence: 99%
“…However, literature suggests that flibanserin’s mechanism of action is primarily due to stimulation of 5-HT 1A receptors. [ 33 39 ] To investigate the relative contribution of 5-HT 1A versus 5-HT 2A receptor occupancy in flibanserin-mediated neuroprotection, we utilized both a pharmacologic blockade of 5-HT 1A receptors and 5-HT 1A knockout mice. Pharmacologic blockade with 10 mg/kg WAY 100635, a 5-HT 1A antagonist, was administered to BALB/c mice 30 minutes prior to a single dose of 6 mg/kg flibanserin.…”
Section: Resultsmentioning
confidence: 99%
“…Flibanserin, marketed as Addyi ™ (Sprout Pharmaceuticals), was recently approved by the Food and Drug Administration (FDA) for the treatment of hypoactive sexual desire disorder (HSDD). [ 28 – 33 ] Seven phase III clinical trials demonstrated that a daily 100 mg dose of flibanserin was safe and resulted in an improvement of HSDD-related symptoms in pre-menopausal women. [ 30 33 ] In CHO cells, flibanserin has a high affinity for serotonergic 5-HT 1A and 5-HT 2A , as well as dopaminergic D 4 receptors, although D 4 receptor binding has yet to be verified in human brain tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Így lehetővé válik, hogy szelektíven csak a tumorsejteket pusztítsuk el, ugyanis a működőképes BRCA1-2-vel rendelkező normál testi sejtek sokkal kevésbé érzékenyek a PARP inhibitorokra [87]. Az Európai Gyógyszer Ügynökség (European Medical Agency, EMA) 2014 decemberében engedélyezte az első PARP inhibitort, az olaparibot (kereskedelmi neve Lynparza), recidiváló, platina-szenzitív serosus petefészek-daganatok harmadik vonalbeli monoterápiájára [88]. A gyógyszer felírási kritériuma a tumor vagy vérmintából igazolt örökletes, vagy szomatikus BRCA1 vagy BRCA2 patogén, illetve nagy valószínűséggel patogén mutáció megléte [89].…”
Section:  Férfi Emlőrák (Bármely éLetkorban)unclassified